ANALISIS IMPLEMENTASI KONSEP MERDEKA BELAJAR DALAM MENGOPTIMALKAN GAYA BELAJAR PESERTA DIDIK PADA PEMBELAJARAN GEOGRAFI DI SMA NEGERI 5 KUPANG - Tael, Adriana Veronika; Pamungkas, Bella Theo Tomi; Sukmawati, Sukmawati (Jurnal Geografi, 2024)
This study aims to (1) find out the implementation of the concept of independent learning on learning geography in 5 Kupang State High School. (2) find out how the learning style of the pupils after applying the idea of free learning on geography learning in 5 kupang State high school. The data collection techniques used in this study are observations, interviews and documentation. Data collected in analysis with the data analysis techniques of Miles and Huberman models, i.e. data reduction, data presentation, conclusion and verification. Based on the results of the research showed that the implementation of the concept of independent learning on learning geography in State High School 5 Kupang experienced excellent progress compared to the previous that can be seen from the readiness of teachers in preparing the teaching equipment and learning ability of students both in class and outside the classroom. The learning style most commonly used by students is the visual learning style. By knowing the learning style, students can help teachers in the learning process so that teachers can teach according to their learning style so that students can understand the given material well.